1985
DOI: 10.1095/biolreprod32.3.584
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Androgen-Induced Proteins in Human Epididymis

Abstract: Androgenic stimulation (0.1 microM testosterone or 5 alpha-dihydrotestosterone in the medium) of cultured human epididymal tubules increased the synthesis of five proteins, identified by their mobility relative to albumin (Ra) in polyacrylamide gels as 0.31, 0.43, 0.67, 0.81 and 1.01. This effect was inhibited by the simultaneous presence of 10 microM cyproterone acetate in the medium. The caput epididymidis was the most active region in the production of these proteins and a gradient of decreasing activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The proximal region or caput epididymidis is particularly active in protein synthesis and secretion, which is consistent with it being the site where the initiation events of sperm maturation occur (Jones et al, 1981;Tezon et al, 1985; 0 1995 WILEY-LISS, INC. 1990). To selectively identify genes expressed in the caput epididymidis, we utilized a caput epididymal-specific probe to screen a mouse epididymal cDNA library.…”
Section: Introductionmentioning
confidence: 53%
“…The proximal region or caput epididymidis is particularly active in protein synthesis and secretion, which is consistent with it being the site where the initiation events of sperm maturation occur (Jones et al, 1981;Tezon et al, 1985; 0 1995 WILEY-LISS, INC. 1990). To selectively identify genes expressed in the caput epididymidis, we utilized a caput epididymal-specific probe to screen a mouse epididymal cDNA library.…”
Section: Introductionmentioning
confidence: 53%
“…Sperm transit time through the epididymis during maturation affords ample exposure to virus particles for absorption (2 (27,28). The absence of virus expression in the testis suggests, however, that if androgens are involved, their influence is mediated through tissue-specific regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Tezon et al [20,21] and Ross et al [22] have also demonstrated that certain androgen-dependent proteins secreted by the epididymis become bound to human spermatozoa. Acquisition of new proteins by the sperm surface during epididymal transit is correlated with the increased capacity of human spermatozoa to bind to zona-free hamster oocytes [23,24].…”
Section: Introductionmentioning
confidence: 98%